Answer:
Simplifying
32 + -8x = 3 + -9x
Solving
32 + -8x = 3 + -9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9x' to each side of the equation.
32 + -8x + 9x = 3 + -9x + 9x
Combine like terms: -8x + 9x = 1x
32 + 1x = 3 + -9x + 9x
Combine like terms: -9x + 9x = 0
32 + 1x = 3 + 0
32 + 1x = 3
Add '-32' to each side of the equation.
32 + -32 + 1x = 3 + -32
Combine like terms: 32 + -32 = 0
0 + 1x = 3 + -32
1x = 3 + -32
Combine like terms: 3 + -32 = -29
1x = -29
Divide each side by '1'.
x = -29
Simplifying
x = -29
Explanation: